Phenolic Acids-Loaded Thermosensitive Hydrogel for Intracanal Biofilm Management - Santos, Vanessa Rodrigues Dos [UNESP]; Caiaffa, Karina Sampaio [UNESP]; Souza, Amanda Caselato Andolfato [UNESP]; Pereira, Jesse Augusto [UNESP]; Abuna, Gabriel Flores; Ribeiro, Tais de Cássia [UNESP]; Bottino, Marco Cícero; Chorili, Marlus [UNESP]; Duque, Cristiane [UNESP] (Elsevier, 2025)
OBJECTIVE: In search of an inter-appointment intracanal medication capable of promoting root canal disinfection while preserving the viability of periapical cells, this study synthesized and characterized chitosan-poloxamer hydrogels (CPH) containing phenolic acids and evaluated their effects on multispecies biofilms and cell viability for potential endodontic use. METHODS: Cinnamic acid (CI), caffeic acid (CA) and controls (calcium hydroxide [CH] and chlorhexidine [CHX]) were incorporated into the CPH matrix. The hydrogels were characterized by flow and oscillatory rheometry, sol-gel transition temperature, compounds release profile and scanning electron microscopy analysis. The effect of hydrogels on multispecies biofilms formed in radicular dentin specimens was evaluated by confocal laser scanning microscopy, while cytotoxicity of CPH containing or not the compounds was assessed using resazurin assays on fibroblasts and macrophages cultures. Statistical analysis was performed with significance determined at p < 0.05. RESULTS: CPHs demonstrated pseudoplastic flow behavior and established a strong gel network at 37° C. Furthermore, hydrogels exhibited thermoresponsive behavior and sustained released of incorporated compounds. All formulations reduced bacterial loads in dentinal multispecies biofilms in dentin tubules, notably, CPH+CA (77.8%) and CPH+CI (73.2%) outperformed CPH+CH (53.6%) and CPH+CHX (39.9%). Overall, all CP hydrogels were cytocompatible when diluted at ratios over 1:4. CPH + CI showed lower cytotoxicity compared to CPH + CA, for both cell lines analyzed. CONCLUSION: CPH demonstrated suitable thermoreversible and physicochemical characteristics to be applied as an injectable temporary medication. When particularly combined with cinnamic acid, it markedly reduced intra-radicular multispecies biofilms and exhibited better cytocompatibility. CLINICAL SIGNIFICANCE: Cinnamic-acid loaded chitosan-poloxamer hydrogel could be an effective intracanal medication for the management of infected root canals in endodontics.